Correlation between hardness and tensile properties in selective electron beam melted Ti-6Al-4V - Lam, Bo Xiang (2016)
Electron beam melting (EBM), a technique of additive manufacturing (AM) has been increasingly studied for the fabrication of Ti-6Al-4V, which exhibits excellent mechanical properties favoured in aerospace, biomedical, marine and offshore applications. This report examines the hardness and strength properties of the alloy of multiple build thickness (10 mm and 20 mm), and establishes a linear correlation of yield strength to microhardness (σ_y vs H_V) and ultimate tensile strength to microhardness (σ_u vs H_V). In agreement with existing literature concerning anisotropic mechanical properties of EBM-fabricated Ti-6Al-4V, it has also been observed through test data that σ_y, σ_u and elongation differs between horizontal and vertical tensile axes. Anisotropy also extends to the modes of failure experienced, with ductile fracture occurring along the vertical tensile axis while brittle fracture happening for horizontally-stretched specimens.